Dietary vitamin D and calcium and periodontitis: A population-based study - Nascimento, Gustavo G.; Leite, Fábio R. M.; Gonzalez-Chica, David A.; Peres, Karen G.; Peres, Marco A. (Frontiers in Nutrition, 2022)
This study aimed to explore the relationship between dietary vitamin D and calcium intake and periodontitis among adults and whether it differs from males to females. Cross-sectional analysis of a population-based cohort study with adults aged 20 to 60 from Southern Brazil. Intake of vitamin D and calcium were gathered in 2012 using two 24h-dietary recalls. Clinical examination assessed the clinical attachment level and bleeding on probing. Confounders included sex, age, family income, smoking, and obesity. The controlled direct effect of vitamin D and calcium on periodontitis was examined using marginal structural modeling. Analyses were also stratified by sex. Of the 1,066 investigated adults (mean age 35±11.7 years; 49% females), 12.3% (95%CI 10.2;14.7) had periodontitis. Calcium intake had a direct protective effect on periodontitis (risk ratio (RR) 0.61; 95%CI 0.45;0.83), whereas no association between vitamin D and periodontitis was observed (RR 1.13; 95%CI 0.82;1.56). Stratified analyses revealed a null association between both vitamin D and calcium intake and periodontitis among men, but a protective association between calcium and intake and periodontitis among women (RR 0.56; 95%CI 0.38;0.79), while vitamin D remained without any association (RR 1.07; 95%CI 0.72;1.61). Our findings suggest a protective association between dietary calcium intake and periodontitis among women.